Vibration damping filler, vibration damping composition containing this vibration damping filler, and vibration damping material and applications

JP2026166729APending Publication Date: 2026-10-14NANAO IND +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2025059874
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0042】 本発明の制振フィラーは、再生可能資源由来の新規なフィラーである。従来の繊維状フィラーは、分散性が低いのに対し、本発明の制振フィラーは、所定温度での加熱後の温度低下の過程で自己集合により繊維を形成する特性を有するため、繊維状フィラーを比較的容易にバインダー中に均一に分散または分布でき、取扱性に優れる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026166729000021
    Figure 2026166729000021
  • Figure 2026166729000022
    Figure 2026166729000022
  • Figure 2026166729000023
    Figure 2026166729000023
Patent Text Reader

Abstract

The present invention provides a novel vibration-damping filler derived from renewable resources, a vibration-damping composition containing the vibration-damping filler, a vibration-damping material, and its applications (vibration-damping method). [Solution] The vibration-damping filler is a compound represented by the following formula (1). TIFF2026166729000019.tif35154 In formula (1), the group R is independently selected from the group consisting of H, an alkyl group having 10 or more carbon atoms, an alkylcarbonyl group having 10 or more carbon atoms, and an acyl group represented by the following formula (2). TIFF2026166729000020.tif27154
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to a vibration-damping filler contained in a vibration-damping material used as a component of a building, such as floors and walls, a vibration-damping composition containing this vibration-damping filler, and a vibration-damping material and its applications. [Background technology]

[0002] There are various noise sources within buildings such as houses. For example, footsteps on the floor, sounds of things falling on the floor, and impact sounds propagate to the floor below, creating noise. These noises are mainly caused by structure-borne sound. On the other hand, there is also noise caused by airborne sound, where sound travels through the air. For example, voices, television sounds, and music can travel through the air between adjacent rooms or between floors, creating noise. Traditionally, soundproofing materials (vibration-damping soundproofing materials or vibration-damping materials, soundproofing materials, sound-absorbing materials, etc.) have been used to block or absorb this type of noise.

[0003] Typically, vibration-damping and sound-insulating materials (hereinafter simply referred to as "vibration-damping materials") contain a material called a vibration-damping filler to improve vibration damping performance. Since vibration-damping materials function to reduce vibrations on solid surfaces by converting vibration energy from the solid surface into thermal energy, flattened fine particles that increase the contact area are considered effective as vibration-damping fillers, and inorganic materials such as mica are widely used.

[0004] For example, Japanese Patent Publication No. 2019-044173 (Patent Document 1) discloses a vibration damping material comprising a urethane acrylate resin as a binder and a vibration damping filler consisting of flat particles with a weight-average particle diameter of 1 to 200 μm and an average aspect ratio of 10 to 100, wherein the loss coefficient η (20°C, third mode) value determined by the cantilever beam method in accordance with JIS K 7391:2008 is 0.02 or higher. Patent Document 1 describes mica as the vibration damping filler.

[0005] Mica is an inorganic material with high density. The mica described in Patent Document 1 is micro-order flat particles with a weight average particle diameter of 1 to 200 μm. Therefore, it is difficult to uniformly disperse such relatively heavy flat particles in a binder, and the mica particles also tend to aggregate with each other, resulting in a heterogeneous system with variations in vibration damping properties. In addition, the micro-order mica of Patent Document 1 cannot provide a sufficiently large contact area with the binder, and the improvement in vibration damping properties may be insufficient depending on the application. Furthermore, mica is also a resource with limited production volume and production locations, and there is a demand for a vibration damping filler that can replace mica.

[0006] Incidentally, as an asphalt modifier derived from renewable resources, Japanese Patent Laid-Open No. 2023-41636 (Patent Document 2) describes a starch-derived asphalt modifier containing a compound of the following formula.

[0007]

Chemical Formula

[0008] (A represents hydrogen or OR, each R is independently an acyl group derived from a linear saturated fatty acid having 10 to 22 carbon atoms, or each R is independently selected from the group consisting of hydrogen, a linear alkyl group having 10 to 22 carbon atoms, an acyl group derived from a linear saturated fatty acid having 10 to 22 carbon atoms, and the following formula:

[0009]

Chemical Formula

[0010] an acyl group derived from the γ-aminobutyric acid derivative represented by the formula, n is 8 to 18, and at least one R is the acyl group derived from the γ-aminobutyric acid derivative)

[0011] The asphalt modifier described in Patent Document 2 states that adding it to asphalt can improve the water resistance and / or non-flowability of asphalt. However, Patent Document 2 does not conduct specific verification of using the asphalt modifier as a vibration damping filler. [Prior Art Documents] [Patent Documents]

[0012] [Patent Document 1] Japanese Unexamined Patent Publication No. 2019-044173 [Patent Document 2] Japanese Unexamined Patent Publication No. 2023-41636 [Summary of Invention] [Problems to be Solved by the Invention]

[0013] Accordingly, an object of the present invention is to provide a novel vibration damping filler (vibration damping material) that can be easily recycled as a resource, a vibration damping composition and a vibration damping material containing the vibration damping filler, and an application (vibration damping method).

[0014] Another object of the present invention is to provide a vibration damping filler that can be easily and uniformly dispersed or present in a binder and has excellent handleability, a vibration damping composition and a vibration damping material containing the vibration damping filler, and an application (vibration damping method).

[0015] Still another object of the present invention is to provide a novel lightweight vibration damping filler having an average diameter (diameter) on the nano or submicron order (less than 1 μm), a vibration damping composition and a vibration damping material containing the vibration damping filler, and an application thereof. [Means for Solving the Problems]

[0016] As a result of intensive studies to achieve the above problems, the present inventors have found a novel vibration damping filler that can be easily recycled as a resource (derived from recyclable resources), and have found that combining the vibration damping filler with a binder can improve the vibration damping property of the vibration damping material, thereby completing the present invention.

[0017] In other words, the present invention includes the following embodiments.

[0018] Embodiment [1]: A vibration-damping filler comprising a compound represented by the following formula (1).

[0019] [ka]

[0020] [In the formula, group R is independently a hydrogen atom, an alkyl group having 10 or more carbon atoms, an alkylcarbonyl group having 10 or more carbon atoms (or an acyl group derived from a saturated fatty acid with 10 or more carbon atoms (including the carbon atoms of the carboxyl group)), and the following formula (2):

[0021] [ka]

[0022] (In the formula, n represents an integer between 8 and 18.) Selected from the group consisting of acyl groups represented by (or acyl groups derived from γ-aminobutyric acid derivatives), Of the aforementioned groups R, at least one group R is either an alkylcarbonyl group having 10 or more carbon atoms, or an acyl group represented by formula (2). m represents either 0 or 1.

[0023] Embodiment [2]: The vibration-damping filler according to Embodiment [1], wherein the alkyl group having 10 or more carbon atoms of the group R is a linear alkyl group having 10 to 22 carbon atoms, and the alkylcarbonyl group having 10 or more carbon atoms of the group R is a linear alkylcarbonyl group having 10 to 22 carbon atoms.

[0024] Embodiment [3]: In formula (1), group R is (i) independently a linear alkylcarbonyl group having 10 to 22 carbon atoms; or, (ii) The vibration-damping filler according to embodiment [1] or [2], wherein at least one of the groups R is an acyl group represented by formula (2).

[0025] Embodiment [4]: ​​The vibration-damping filler according to any of Embodiments [1] to [3], wherein the hydrogen atom group R in formula (1) is one or less.

[0026] Embodiment [5]: In formula (1), the group R is (i) independently a linear alkylcarbonyl group having 12 to 20 carbon atoms; or, (ii) The vibration-damping filler according to any of the embodiments [1] to [4], which is independently an acyl group represented by formula (2).

[0027] Embodiment [6]: A vibration damping filler according to any of Embodiments [1] to [5], wherein in formula (2), n is an integer from 10 to 16.

[0028] Embodiment [7]: The vibration-damping filler according to any one of Embodiments [1] to [6], wherein the compound represented by formula (1) is a compound represented by the following formula (3) or (4).

[0029] [ka]

[0030] (In the formula, base R is the same as in formula (1) above)

[0031] [ka]

[0032] (In the formula, base R is the same as in formula (1) above)

[0033] Embodiment [8]: A vibration damping composition comprising at least a vibration damping filler according to any of Embodiments [1] to [7] and a binder.

[0034] Embodiment [9]: The vibration damping composition according to Embodiment [8], comprising the vibration damping filler in a ratio of 0.05 to 50 parts by mass per 100 parts by mass of the binder.

[0035] Embodiment

[10] : The vibration-damping composition according to Embodiment [8] or [9], wherein the binder comprises asphalt.

[0036] Embodiment

[11] : A vibration damping material formed from a vibration damping composition according to any of Embodiments [8] to

[10] , wherein the compound represented by formula (1) forms a fibrous phase (or fibrous phase).

[0037] Embodiment

[12] : The vibration damping material according to Embodiment

[11] , wherein the average fiber diameter of the fibers in the fiber phase is 10 to 500 nm, and the ratio of the average fiber length to the average fiber diameter of the fibers in the fiber phase (average fiber length / average fiber diameter) is 10 or more.

[0038] Embodiment

[13] : A method for manufacturing a vibration damping material according to Embodiment

[11] or

[12] , comprising heating and mixing at least a binder with a vibration damping filler according to any of Embodiments [1] to [7].

[0039] Embodiment

[14] : A method for suppressing vibrations originating from vibration sources by installing the vibration damping material described in Embodiment

[11] or

[12] in a building.

[0040] In this specification and in the claims, the term “renewable resources” means resources that are regenerated in natural cycles and can be sustainably utilized. Typical renewable resources are organic resources (biological resources) derived from living organisms (animals and plants) that can be regenerated (reused or replenished), and unlike fossil fuels (oil, coal, natural gas, etc.), which are depletable resources, they can be used indefinitely.

[0041] In this specification and in the claims, the "number of carbon atoms" in "linear saturated fatty acid having X to Y carbon atoms" means the number of carbon atoms including the carbon atoms of the carboxyl group of the fatty acid. [Effects of the Invention]

[0042] The vibration-damping filler of the present invention is a novel filler derived from renewable resources. Unlike conventional fibrous fillers, which have poor dispersibility, the vibration-damping filler of the present invention has the property of forming fibers by self-assembly during the temperature decrease process after heating at a predetermined temperature. Therefore, the fibrous filler can be relatively easily and uniformly dispersed or distributed in the binder, and it has excellent handling properties.

[0043] Furthermore, because the vibration-damping filler of the present invention is an organic material, it is lightweight (or low density), and the average diameter of the fibers is on the nano or submicro order (less than 1 μm), resulting in a large contact area with the binder, which is advantageous for improving vibration damping performance. [Brief explanation of the drawing]

[0044] [Figure 1A] Figure 1A is an AFM image (height image) of the vibration damping material prepared in Example 1. [Figure 1B] Figure 1B shows the AFM image (error signal image) of the damping material prepared in Example 1. [Figure 2A] Figure 2A is an AFM image (height image) of the vibration damping material prepared in Example 2. [Figure 2B] Figure 2B shows the AFM image (error signal image) of the damping material prepared in Example 2. [Figure 3A] Figure 3A shows the AFM image (height image) of the vibration damping material (blown asphalt) prepared in Comparative Example 1. [Figure 3B] Figure 3B shows the AFM image (error signal image) of the vibration damping material (blown asphalt) prepared in Comparative Example 1. [Figure 4A] Figure 4A shows the AFM image (height image) of the vibration damping material prepared in Reference Example 1. [Figure 4B] Figure 4B shows the AFM image (error signal image) of the damping material prepared in Reference Example 1. [Modes for carrying out the invention]

[0045] The mechanism by which the vibration-damping filler of the present invention can improve the vibration-damping properties of vibration-damping materials is unknown, but it can be estimated as follows.

[0046] "Vibration damping" refers to the process of converting the vibrational energy of an object into thermal energy, thereby reducing the vibration of the object and the energy released as sound. A representative index for evaluating this vibration damping performance is the loss factor η. It is known that a larger loss factor η indicates higher vibration damping (or vibration suppression) ability and superior vibration damping performance.

[0047] The vibration-damping filler of the present invention, which is a compound represented by formula (1) above (hereinafter sometimes simply referred to as "compound (1)"), is heated to a predetermined temperature and then, as the temperature decreases, self-assembles in the binder (matrix) phase to form fibers in a specific direction (or having orientation) throughout the entire binder. That is, compound (1) forms a phase-separated structure by self-assembling in the binder phase, and forms a fibrous phase (fibrous phase or dispersed phase) [forming intricately intertwined fibers (fibrous structure or fiber aggregate (three-dimensional network structure)) throughout the entire binder].

[0048] In particular, since the average diameter of the aforementioned fibers is on the nano or submicro order (for example, around 10-500 nm), the surface area, i.e., the contact area with the object being damped, is larger than that of micro-order damping fillers, and the loss coefficient η is also larger.

[0049] Furthermore, when the fibrous vibration-damping filler (especially compound (1)) vibrates, the friction between the vibration-damping fillers increases, allowing vibration energy to be consumed as thermal energy. This further increases the loss coefficient η, and it can be estimated that vibration damping performance can be effectively improved.

[0050] In other words, the vibration-damping filler of the present invention can also be described as a vibration-damping filler with an average diameter (especially the average fiber diameter) of nanometers (less than 1 μm) or submicrometers (for example, 100 nm or more and less than 1 μm).

[0051] [Vibration damping filler] The vibration damping filler of the present invention is given by the following formula (1):

[0052] [ka]

[0053] [In the formula, group R is independently a hydrogen atom, an alkyl group having 10 or more carbon atoms, an alkylcarbonyl group having 10 or more carbon atoms, and the following formula (2):

[0054] [ka]

[0055] (In the formula, n represents an integer between 8 and 18.) Selected from the group consisting of acyl groups represented by, Of the aforementioned groups R, at least one group R is either an alkylcarbonyl group having 10 or more carbon atoms, or an acyl group represented by formula (2). m represents either 0 or 1. It consists of compounds represented by [formula].

[0056] The compound represented by formula (1) above is derived from renewable resources.

[0057] In formula (1) above, the alkyl group R having 10 or more carbon atoms (linear or branched alkyl group) is, for example, a linear or branched C group such as a decyl group, undecyl group, dodecyl group, tridecyl group, tetradecyl group, pentadecyl group, hexadecyl group, heptadecyl group, octadecyl group, nonadecyl group, eicosyl group, heneicosyl group, or docosyl group. 10-22 Alkyl alkyl groups, preferably linear or branched C 12-20 Alkyl alkyl groups, more preferably linear or branched C 14-20 Alkyl group, more preferably linear or branched C 16-18 Alkyl groups (especially linear C groups such as hexadecyl and octadecyl groups) 16-18 Examples include alkyl groups.

[0058] The alkylcarbonyl group having 10 or more carbon atoms in group R (the number of carbon atoms including the carbon atom of the carbonyl group) (the saturated fatty acid having 10 or more carbon atoms (the number of carbon atoms including the carbon atom of the carboxyl group) (linear or branched saturated fatty acid) (R 1 acyl group derived from COOH))(R 1 CO-) includes, for example, linear or branched C such as decanoic acid (capric acid), undecanoic acid (undecylic acid, undecanoic acid), dodecanoic acid (lauric acid), tridecanoic acid (tridecylic acid, tridecanoic acid), tetradecanoic acid (myristic acid), pentadecanoic acid (pentadecylic acid), hexadecanoic acid (palmitic acid), heptadecanoic acid (margaric acid), octadecanoic acid (stearic acid), nonadecanoic acid (nonadecylic acid), icosanoic acid (arachidic acid, eicosanoic acid), heneicosanoic acid (heneicosylic acid, heneicosanoic acid) and docosanoic acid (behenic acid) 10-22 saturated fatty acids, preferably linear or branched C 12-20 saturated fatty acids, more preferably linear or branched C 14-20 saturated fatty acids, even more preferably linear or branched C 16-18 saturated fatty acids (particularly acyl groups derived from linear C such as hexadecanoic acid (palmitic acid), octadecanoic acid (stearic acid) 16-18 saturated fatty acids), and the like.

[0059] In the above formula (2), n is an integer of 8 to 18, preferably an integer of 10 to 16, and more preferably an integer of 12 to 16.

[0060] That is, the acyl group represented by the above formula (2) (the acyl group derived from the γ-aminobutyric acid (GABA) derivative (R represented by the above formula (2)) 2 C(=O)NH(CH2)3COOH))(R 2Examples of C(=O)NH(CH2)3CO- include 4-[(1-oxononyl)amino]butanoic acid, 4-[(1-oxodecyl)amino]butanoic acid, 4-[(1-oxoundecyl)amino]butanoic acid, 4-[(1-oxododecyl)amino]butanoic acid, 4-[(1-oxotridecyl)amino]butanoic acid, 4-[(1-oxotetradecyl)amino]butanoic acid, 4-[(1-oxopentadecyl)amino]butanoic acid, 4-[(1-oxohexadecyl)amino]butanoic acid, 4-[(1-oxoheptadecyl)amino]butanoic acid, 4-[(1-oxooctadecyl)amino]butanoic acid, and 4-[(1-oxononadecyl)amino]butanoic acid. 14-24 Examples include acyl groups derived from GABA derivatives (where n in formula (2) is an integer from 8 to 18), and preferably C 16-22 An acyl group derived from a GABA derivative (where n is an integer from 10 to 16), more preferably a C such as 4-[(1-oxotetradecyl)amino]butanoic acid. 18-22 This is an acyl group derived from a GABA derivative (where n is an integer between 12 and 16).

[0061] Typical groups R include linear C such as hexadecanoic acid (palmitic acid) and octadecanoic acid (stearic acid). 16-18 Acyl groups corresponding to saturated fatty acids, such as 4-[(1-oxotetradecyl)amino]butanoic acid, etc. 18-22 Examples include acyl groups derived from GABA derivatives.

[0062] The four bases R (five bases R if m is 1) in formula (1) above may be the same or different from each other, but it is preferable that they are all the same.

[0063] The compound represented by formula (1) may be any compound in which at least one group R is either an acyl group derived from a linear saturated fatty acid having 10 to 22 carbon atoms, or an acyl group derived from a γ-aminobutyric acid derivative represented by formula (2). For example, the group R may be (i) independently an acyl group derived from a linear saturated fatty acid having 10 to 22 carbon atoms, or (ii) at least one of the groups R is an acyl group derived from the γ-aminobutyric acid derivative.

[0064] Furthermore, in compound (1), the number of hydrogen atom-representing groups R among the four groups R (five groups R if m is 1) is, for example, two or less, preferably one or less (i.e., 0 or 1), and especially 0. A small number of hydrogen atom-representing groups R increases hydrophobicity, improves compatibility with binders (especially asphalt), and facilitates crystallization, making separation and purification easier, which is advantageous.

[0065] In other words, in compound (1), group R is (i) independently an acyl group (linear alkylcarbonyl group) derived from a linear saturated fatty acid having 10 to 22 carbon atoms, or (ii) independently selected from the group consisting of a linear alkyl group having 10 to 22 carbon atoms, an acyl group (linear alkylcarbonyl group) derived from a linear saturated fatty acid having 10 to 22 carbon atoms, and an acyl group derived from a γ-aminobutyric acid derivative represented by formula (2) (where n is an integer from 8 to 18), and preferably at least one group R is an acyl group derived from the γ-aminobutyric acid derivative (where n is an integer from 8 to 18);

[0066] More preferably, group R is (i) independently an acyl group (linear alkylcarbonyl group) derived from a linear saturated fatty acid having 10 to 22 carbon atoms (e.g., 12 to 20 carbon atoms), or (ii) independently an acyl group derived from a γ-aminobutyric acid derivative represented by formula (2) (where n is an integer from 8 to 18);

[0067] More preferably, group R is (i) an acyl group (linear alkylcarbonyl group) derived from the same linear saturated fatty acid having 10 to 22 carbon atoms (for example, 12 to 20, preferably 14 to 20), or (ii) an acyl group derived from the same γ-aminobutyric acid derivative represented by formula (2) (where n is an integer from 8 to 18, preferably an integer from 10 to 16).

[0068] In formula (1) above, m represents 0 or 1. When m is 0 (i.e., unsubstituted or with a hydrogen atom bonded), compound (1) is 1,5-anhydroglucitol or its derivatives, or stereoisomers (enantiomers, diastereomers) thereof. When m is 1, compound (1) is glucopyranose or its derivatives, or stereoisomers (enantiomers, diastereomers) thereof.

[0069] Of these compounds (1), it is preferable that they are 1,5-anhydro-D-glucitol (1,5-AG) represented by the following formula (3) or its derivatives, or D-glucopyranose (Glc) represented by the following formula (4) or its derivatives, or stereoisomers thereof, due to their naturally occurring nature, lack of reducing properties, and stability.

[0070] [ka]

[0071] (In the formula, base R is the same as in formula (1) above)

[0072] [ka]

[0073] (In the formula, base R is the same as in formula (1) above)

[0074] Representative compounds (1) include 1,5-anhydro-D-glucitol-2,3,4,6-O-tetrapalmitate, in which the group R in formula (3) is an acyl group derived from the same C16 linear saturated fatty acid [hexadecanoic acid (palmitic acid)]; 1,5-anhydro-D-glucitol-2,3,4,6-O-tetrastearate, in which the group R in formula (3) is an acyl group derived from the same C18 linear saturated fatty acid [octadecanoic acid (stearic acid)]; and 1,5-anhydro-2,3,4,6-tetra-O-{4-[(1-oxotetradecyl)amino]butanoyl}-D-glucitol, in which the group R in formula (3) is an acyl group derived from the same γ-aminobutyric acid derivative (n is 14) [4-[(1-oxotetradecyl)amino]butanoic acid].

[0075] The compound (1) may be synthesized by a general method, for example, by a method described in Japanese Patent Publication No. 6952305.

[0076] [Vibration damping composition] The present invention encompasses a vibration damping composition comprising at least the vibration damping filler and a binder.

[0077] (binder) The binder is not particularly limited and may be an inorganic binder or an organic binder, but an organic binder is preferred in terms of handling and moldability of the vibration damping material. Examples of organic binders include bituminous substances, soft resins, or elastomer components.

[0078] Examples of bituminous materials include asphalt, coal tar, and pitch. These bituminous materials can be used individually or in combination of two or more. Of these, asphalt is preferred.

[0079] The asphalt is not particularly limited and can include general asphalts such as natural asphalt (e.g., lake asphalt, rock asphalt, oil sand, asphaltite, etc.) and petroleum asphalt (e.g., straight asphalt, blown asphalt, etc.). These asphalts can be used individually or in combination of two or more types. Of these asphalts, petroleum asphalt such as blown asphalt is preferred.

[0080] The aforementioned asphalt may be used as modified asphalt by combining it with a modifier. The modifier includes organic modifiers and inorganic modifiers.

[0081] Examples of organic modifiers include polyolefins, vinyl polymers (e.g., polyvinyl chloride, acrylic resin, polyvinyl acetate, ethylene-vinyl acetate copolymer, ethylene-vinyl alcohol copolymer, ethylene-acrylic acid copolymer, ethylene-methyl acrylate copolymer, ethylene-ethyl acrylate copolymer, etc.), polyamides, polyesters, synthetic rubber or elastomers (e.g., polybutadiene, polyisoprene, styrene-butadiene copolymers such as styrene-butadiene-styrene block copolymer, etc.), natural rubber, tackifiers (e.g., terpene resins, rosin resins such as natural rosin and modified rosin, petroleum resins, modified olefin polymers, etc.), and oils and fats (e.g., naphthenic raw material oils, etc.). These organic modifiers can be used individually or in combination of two or more.

[0082] Examples of inorganic modifiers include metal particles (powder) such as iron, copper, tin, zinc, nickel, and stainless steel; metal oxide particles such as iron oxide, iron(III) oxide, iron(III) oxide, ferrite, tin oxide, zinc oxide, zinc oxide, copper oxide, and aluminum oxide; metal salt particles such as barium sulfate, calcium sulfate, aluminum sulfate, calcium sulfite, calcium carbonate, calcium bicarbonate, barium carbonate, and magnesium hydroxide; mineral particles such as steelmaking slag, slate chips, mica, clay, talc, wollastonite, diatomaceous earth, silica sand, pumice powder, silica balloons, glass balloons, and shirasu balloons; and inorganic fibers such as glass fibers and carbon fibers. These inorganic modifiers can be used individually or in combination of two or more.

[0083] Among these modifiers, organic modifiers such as elastomers (thermoplastic elastomers), tackifiers, and oils and fats are preferred, and styrene-diene copolymers such as styrene-butadiene-styrene block copolymers are particularly preferred.

[0084] The penetration degree of asphalt (1 / 10 mm) can be selected from a range of approximately 0 to 300 according to the method in accordance with JIS K 2207-1996, for example, 5 to 150, preferably 7 to 80, and more preferably 10 to 20.

[0085] The softening point of asphalt can be selected from a range of approximately 20 to 200°C according to a method conforming to JIS K 2207-1996, for example, 40 to 170°C, preferably 60 to 140°C, and more preferably 90 to 120°C.

[0086] Examples of soft resin or elastomer components include polyolefins, vinyl polymers (e.g., polyvinyl chloride, ethylene-vinyl acetate copolymer, ethylene-vinyl alcohol copolymer, ethylene-acrylic acid copolymer, ethylene-methyl acrylate copolymer, ethylene-ethyl acrylate copolymer, etc.), polyamide elastomers, polyester elastomers, synthetic rubbers (e.g., polybutadiene, polyisoprene, styrene-butadiene copolymer, etc.), natural rubber, and rosin resins (e.g., natural rosin, modified rosin, etc.). These soft resin or elastomer components can be used individually or in combination of two or more. Of these, styrene-diene copolymers such as styrene-butadiene block copolymers are preferred.

[0087] These binders can be used individually or in combination of two or more types. Of these, it is preferable that the binder contains asphalt due to its excellent vibration damping properties.

[0088] The proportion of asphalt in the binder may be 10% by mass or more, for example, 30% by mass or more, preferably 50% by mass or more, more preferably 70% by mass or more, more preferably 80% by mass or more, most preferably 90% by mass or more, and may even be 100% by mass. If the proportion of asphalt in the binder is too low, the vibration damping performance of the damping material may decrease.

[0089] The binder may be a combination of asphalt and a soft resin or elastomer component, and the proportion of the soft resin or elastomer component may be 100 parts by mass or less per 100 parts by mass of asphalt, for example 1 to 80 parts by mass, preferably 3 to 50 parts by mass, and more preferably 5 to 40 parts by mass.

[0090] From the viewpoint of the vibration damping properties of the damping material, it is most preferable for the binder to consist solely of asphalt.

[0091] The density of the binder is, for example, 0.5 to 2 g / cm³. 3 Preferably 0.7 to 1.5 g / cm³3 More preferably 0.8 to 1.3 g / cm³ 3 Most preferably 0.9 to 1.1 g / cm³ 3 If the binder density is too low, there is a risk of reduced vibration damping performance, and if it is too high, there is a risk of reduced lightness.

[0092] The proportion of the binder can be selected from a range of approximately 5 to 95% by mass in the vibration damping composition, for example, 10 to 90% by mass, preferably 20 to 85% by mass, more preferably 30 to 80% by mass, more preferably 50 to 75% by mass, and most preferably 60 to 70% by mass. If the proportion of binder is too low, the workability may decrease, and if it is too high, the lightweight properties may decrease.

[0093] The vibration-damping filler of the present invention (particularly compound (1)) has excellent compatibility with the binder (particularly asphalt), and the vibration-damping filler is easily and uniformly dispersed in the binder within the composition.

[0094] The proportion of the vibration-damping filler (especially compound (1)) may be, for example, about 0.05 to 50 parts by mass per 100 parts by mass of binder, preferably 0.1 to 50 parts by mass (e.g., 0.3 to 40 parts by mass), more preferably 0.5 to 50 parts by mass (e.g., 0.7 to 35 parts by mass), more preferably 1 to 50 parts by mass (e.g., 2 to 30 parts by mass), and most preferably 5 to 50 parts by mass (e.g., 7 to 25 parts by mass). Furthermore, the proportion of the vibration-damping filler (especially compound (1)) in the vibration-damping composition is, for example, 0.1 to 80% by mass, preferably 0.5 to 70% by mass, more preferably 1 to 60% by mass, more preferably 1.5 to 50% by mass, and most preferably 2 to 40% by mass. If the proportion of the vibration-damping filler is too small, there is a risk that the vibration-damping performance cannot be sufficiently improved, and if it is too large, there is a risk that the vibration-damping filler cannot be sufficiently mixed, dissolved, or dispersed.

[0095] The vibration damping composition of the present invention may contain, in addition to the vibration damping filler and binder, other vibration damping fillers, fillers, and conventional additives, as long as the effects of the invention are not impaired.

[0096] (Other vibration-damping fillers) Other vibration-damping fillers can be general-purpose ones, as long as they have vibration-damping properties.

[0097] Other vibration-damping filler materials include metals such as iron, copper, aluminum, tin, zinc, nickel, stainless steel or alloys containing these, inorganic oxides or metal oxides (e.g., beryllium oxide, magnesia, silicon oxide or silica, aluminum oxide or alumina, titania, zirconia, magnesia, manganese oxide, zinc oxide, zinc oxide, copper oxide, tin oxide, iron oxide, iron(III) oxide, iron(III) oxide, ferrite, antimony oxide, cerium oxide, tin-doped indium oxide (ITO), etc.), nitrogen compounds (e.g., boron nitride, aluminum nitride, silicon nitride, carbon nitride, titanium nitride, etc.), carbon compounds (e.g., silicon carbide, fluorine carbide, boron carbide, titanium carbide, tungsten carbide, diamond, etc.), minerals (e.g., talc, mica, zeolite, ferrite, tourmaline, diatomaceous earth, calcined siliceous earth, activated clay, kaolin, pyrophila Examples of materials include inorganic materials such as lithoplasm, sericite, bentonite, smectite, montmorillonite, clay, red iron oxide, quartz, wollastonite, etc., glass (e.g., soda-lime glass, lead glass, borosilicate glass, silica glass, etc.), silicon, and graphite; and organic materials such as polyolefin resins (e.g., polyethylene, polypropylene, etc.), styrene resins (e.g., polystyrene, ABS resin, etc.), (meth)acrylic resins (e.g., polymethyl methacrylate, etc.), vinyl chloride resins (e.g., polyvinyl chloride, polyvinylidene chloride, etc.), polyamide resins (e.g., polyamide 6, polyamide 66, etc.), polyester resins (e.g., polyethylene terephthalate, polybutylene terephthalate, etc.), cellulose resins (e.g., cellulose, cellulose acetate, etc.), and natural materials (plant materials, animal materials, etc.).

[0098] The shape of the other vibration-damping fillers is not particularly limited, but particulate (especially flattened particulate), fibrous, or hollow is preferred.

[0099] Other specific vibration-damping fillers include, for example, metal particles such as iron, copper, aluminum, or alloys containing these; mineral particles such as talc and mica; inorganic fibers such as glass fibers and carbon fibers; natural fibers such as cotton and hemp; chemical fibers (regenerated fibers such as rayon, synthetic fibers such as polyester fibers and polyamide fibers, etc.); and hollow microparticles of inorganic materials such as silica balloons, shirasu balloons, and glass balloons.

[0100] These other vibration-damping fillers can be used individually or in combination of two or more. Of these other vibration-damping fillers, hollow microparticles (hollow microparticles of inorganic material) are preferred from the viewpoint of improving vibration damping performance.

[0101] The hollow shape of the hollow microparticles may be a porous shape like pumice powder or a connected hollow shape (or open-cell shape), but from the standpoint of high vibration damping, a hollow shape having one or more sealed hollow parts (cavities) inside the microparticles (closed hollow shape or closed-cell shape) is preferred, and a balloon shape is particularly preferred.

[0102] In this specification and in the claims, "balloon shape" means a hollow shape having a single sealed cavity like a balloon.

[0103] Inorganic hollow fine particles are preferred because they easily improve vibration damping, silica balloons, shirasu balloons, and glass balloons are more preferred, and glass balloons are even more preferred because they easily improve vibration damping and cost-effectiveness.

[0104] The average particle size (volume average particle size) of the hollow microparticles may be 500 μm or less, for example, 300 μm or less, preferably 200 μm or less, more preferably 150 μm or less, and more preferably 100 μm or less. Specifically, it is 10 to 300 μm, preferably 15 to 200 μm, more preferably 20 to 150 μm, more preferably 30 to 100 μm, and most preferably 50 to 80 μm. If the average particle size is too small, the vibration damping performance may decrease, and if it is too large, the moldability of the vibration damping material may decrease. In this specification and in the claims, the average particle size of the hollow microparticles can be measured on a volume basis using a laser diffraction particle size distribution analyzer.

[0105] The vibration damping performance of the present invention can be improved by combining a vibration damping filler with an average diameter (diameter) of the nano or submicro order with other vibration damping fillers (especially vibration damping fillers of the micro order).

[0106] The proportion of other vibration-damping fillers is, for example, 70% by mass or less, preferably 60% by mass or less, more preferably 50% by mass or less, and more preferably 40% by mass or less (for example, 0.1 to 30% by mass) in the vibration-damping composition.

[0107] (Filler) The vibration-damping composition of the present invention may further contain a filler. The filler may be an inorganic filler or an organic filler.

[0108] Examples of inorganic fillers include metal salt particles (e.g., barium sulfate, calcium sulfate, aluminum sulfate, calcium sulfite, calcium carbonate, calcium bicarbonate, barium carbonate, magnesium hydroxide, etc.).

[0109] Examples of organic fillers include wood flour, pulp, and cross-linked resin particles (such as cross-linked polyethylene particles, cross-linked polystyrene particles, and cross-linked acrylic particles).

[0110] These fillers can be used individually or in combination of two or more. Of these fillers, inorganic fillers are preferred because they improve the moldability of the damping material and make it easier to achieve both workability and damping properties, metal salt particles are more preferred, and metal carbonate salts such as calcium carbonate are even more preferred.

[0111] The average particle size (volume-average particle size) of the filler (especially inorganic fillers) is, for example, 10 to 300 μm, preferably 20 to 200 μm, more preferably 30 to 150 μm, and more preferably 50 to 100 μm. If the average particle size of the filler is too small, the moldability of the damping material may decrease, and if it is too large, the mechanical properties of the damping material may decrease. In this specification and in the claims, the average particle size of the filler can be measured on a volume basis using a laser diffraction particle size distribution analyzer.

[0112] The shape of the filler is not particularly limited and may be granular, irregularly shaped, fibrous, etc., but granular is preferred in terms of handling and dispersibility.

[0113] The proportion of the filler is, for example, 80% by mass or less, preferably 65% ​​by mass or less, more preferably 50% by mass or less, and more preferably 35% by mass or less (for example, 1 to 20% by mass) in the vibration damping composition. If the proportion of the filler is too high, the lightness, workability, and vibration damping performance may decrease.

[0114] Conventional additives can be used, such as stabilizers (heat stabilizers, UV absorbers, light stabilizers, antioxidants, etc.), thickeners, flame retardants, plasticizers, antistatic agents, colorants, surfactants, dispersants, lubricants, crystallization rate retarders, lubricants, antibacterial agents, insecticides (anticides, mite repellents, etc.), preservatives (fungicides, etc.), matting agents, heat storage agents, fragrances, fluorescent whitening agents, and wetting agents.

[0115] These additives can be used individually or in combination of two or more. The total proportion of the additives in the vibration damping composition may be, for example, 40% by mass or less, preferably 20% by mass or less, and more preferably 10% by mass or less (for example, 0.1 to 5% by mass), and the total proportion of the additives may be, for example, about 0.2 to 1% by mass.

[0116] As described above, the vibration-damping filler of the present invention (particularly compound (1)) has excellent compatibility with binders (particularly asphalt), and is easily and uniformly dispersed in the binder in the composition, resulting in a homogeneous composition (vibration-damping composition).

[0117] (vibration damping material) The vibration damping material of the present invention is formed from the vibration damping composition. When the vibration damping composition is heated to a predetermined temperature, as the temperature subsequently decreases, the vibration damping fillers in the composition (particularly compound (1)) self-assemble and grow into fibrous structures in a specific direction (or having orientation), forming a structure in which the fibers are intertwined, and forming a structure [fibrous phase (fibrous phase or dispersed phase)] that is phase-separated from the binder (or matrix) phase formed by the binder [forming a complexly intertwined fibrous phase (fibrous structure or fibrous aggregate (three-dimensional network structure)) throughout the binder]. In other words, the vibration damping material of the present invention is a vibration damping material (a vibration damping material with a fibrous phase formed (a three-dimensional network-like vibration damping material)) in which the fibers of the fibrous phase are uniformly distributed in the binder without uneven distribution (the fibers maintain even spacing).

[0118] In other words, in the vibration damping material, the fibers of the vibration damping filler (especially the compound (1)) (fibers with an average diameter of nano or submicro order) are formed throughout the entire vibration damping material, and the fibers are intricately intertwined to form a three-dimensional fiber aggregate (fiber phase). As a result, the contact area with the binder increases, and it is possible that this also contributes to changes in the structure and physical properties of the binder, thus improving the vibration damping performance.

[0119] In the vibration damping material, the vibration damping filler (particularly compound (1)) consists of fibers grown in a specific direction [or oriented (distributed, dispersed) fibers] that are intricately intertwined, forming a fibrous phase (fibrous phase or dispersed phase) in the binder phase. That is, the fibers are formed with orientation and, in the composition, form a fibrous aggregate (fibrous phase) with uniform (almost uniform) spacing without clumping. The fibers in such a fibrous phase are long fibers with an average fiber length based on atomic force microscopy (AFM) images of, for example, 50 μm or more, preferably 70 μm or more, and more preferably 100 μm or more. The average fiber diameter is, for example, 10 to 500 nm, preferably 30 to 400 nm, and more preferably 50 to 300 nm.

[0120] The average fiber length and average fiber diameter can be calculated as the average of 10 points based on atomic force microscope (AFM) images of the vibration damping material.

[0121] The ratio of the average fiber length to the average fiber diameter (average fiber length / average fiber diameter) of the aforementioned fibers may be, for example, 10 or more, preferably 15 or more, and more preferably 20 or more (for example, 100 or more). In the present invention, the vibration-damping filler (compound (1)) may self-assemble to form long fibers and form a three-dimensional network structure.

[0122] Normally, when fibrous materials are added to a binder (especially asphalt) and dispersed within the binder, the fibers interfere with each other (contact) and become entangled, making uniform dispersion or distribution difficult and resulting in inconsistent vibration damping performance. However, in the homogeneous vibration damping material of the present invention, granular compounds are uniformly mixed and then self-assembled to form fibers (fibrous material). Therefore, even though they are fibrous, they do not become entangled and clump together, and can be uniformly distributed (at uniform intervals) within the binder. In particular, uniform distribution becomes difficult as the fiber length increases, but in the vibration damping material of the present invention, long fibrous vibration damping fillers can be distributed within the binder phase without aggregation, resulting in stable vibration damping performance throughout the entire vibration damping material.

[0123] The proportion of the vibration-damping filler (particularly compound (1)) in the vibration-damping material may be the same as the proportion of the vibration-damping filler (particularly compound (1)) in the vibration-damping composition, including preferred embodiments. If the proportion of the vibration-damping filler is too small, there is a risk that the vibration-damping performance will not be sufficiently improved, and if it is too large, there is a risk that the vibration-damping filler will not be sufficiently mixed and dissolved.

[0124] The aforementioned vibration damping material is lightweight and has a density of 2.5 g / cm³. 3 The following (especially 2g / cm³) 3 The following may also be acceptable, for example, 1.5 g / cm³ 3 Preferably, 1.3 g / cm³ 3 More preferably, 1 g / cm³ 3 More preferably, 0.8 g / cm³ 3 Below, the most preferred concentration is 0.7 g / cm³. 3 The following applies. The specific density range is, for example, 0.1 to 1.3 g / cm³. 3 Preferably 0.3 to 1 g / cm³ 3 More preferably 0.4 to 0.9 g / cm³ 3 , more preferably 0.5~0.8 g / cm³ 3 Most preferably 0.6 to 0.7 g / cm³ 3 Therefore, if the density of the damping material is too high, there is a risk that the damping properties and lightweight nature will decrease.

[0125] In this specification and in the claims, the density of the vibration damping material can be measured by the method described in the examples below.

[0126] (Manufacturing method for vibration damping materials) Such vibration damping materials can be manufactured by heating and mixing (kneading) at least a binder (especially asphalt) and the vibration damping filler. In other words, the method for manufacturing the vibration damping material only needs to include at least a mixing step of mixing the vibration damping filler and the binder, and a heating step of heating the binder (especially asphalt).

[0127] In the mixing step, a desired amount of the vibration-damping filler can be added to the binder (especially asphalt) and mixed using a general method, for example, by using a mixing device such as a mixer.

[0128] In the heating step, the heating temperature may be, for example, around 80 to 250°C, preferably 90 to 240°C, and more preferably 100 to 230°C. The heating time may be, for example, around 30 seconds to 1 hour, preferably 1 to 45 minutes, and more preferably 1.5 to 40 minutes.

[0129] The vibration-damping filler of the present invention (compound (1)) is heated to a predetermined temperature, and then self-assembles to form fibers (or a fibrous phase) as the temperature decreases (or cools). The heated vibration-damping filler (compound (1)) may be cooled by air cooling, and the cooling rate may be controlled. The cooling rate is, for example, 1 to 8°C / min, preferably 1.5 to 7.5°C / min (for example, 2 to 7°C / min), and more preferably about 3 to 6°C / min. The cooling rate may be the average cooling rate during the cooling operation, for example, the rate obtained by dividing the change in temperature from the end of heating to the end of cooling (usually room temperature) by the total cooling time. Air cooling (natural cooling) is preferred.

[0130] The vibration damping material of the present invention may be manufactured in the order of the mixing step followed by the heating step, or in the order of the heating step followed by the mixing step. When the vibration damping material is manufactured in the order of the heating step followed by the mixing step, it is preferable that the mixing step be performed simultaneously (or nearly simultaneously) with the heating step in order to effectively utilize the spontaneous fiber-forming ability of the vibration damping filler (particularly compound (1)).

[0131] Specifically, the vibration damping material of the present invention may be manufactured by heating a mixture (i.e., a vibration damping composition) obtained by adding and mixing the vibration damping filler with a binder, thereby changing the vibration damping filler into a fibrous form; or it may be manufactured by heating the binder, adding and mixing the vibration damping filler, particularly by adding and mixing it almost simultaneously with the heating operation of the heating step, thereby changing the vibration damping filler into a fibrous form.

[0132] The vibration damping material of the present invention can be manufactured by a simple operation of heating and mixing (or kneading) by utilizing the spontaneous fiber-forming ability of the vibration damping filler (particularly compound (1)), and offers excellent productivity.

[0133] The vibration damping material of the present invention may be molded into a desired shape by conventional methods. The shape is not particularly limited and can be selected according to the application, and may be one-dimensional, such as linear or thread-like, two-dimensional, such as film-like, sheet-like, or plate-like, or tertiary, such as block-like, rod-like, tubular, or tube-like. For example, a vibration damping composition containing a binder and a vibration damping filler may be heated and mixed (melt-kneaded) and molded into a layered (or sheet-like) form.

[0134] The vibration damping material of the present invention may include, for example, a vibration damping layer formed of the vibration damping composition, or it may be a single-layer sheet formed by the vibration damping layer alone, or it may be a laminated sheet of the vibration damping layer and other layers. The other layers may be laminated on at least one surface of the vibration damping layer, or it may be a combination of a surface layer laminated on one surface of the vibration damping layer and a back layer laminated on the other surface. Furthermore, the surface layer and the back layer may each be a single-layer structure or a laminated structure of two or more layers. When the surface layer and the back layer each have a laminated structure, there may be an adhesive layer between the outermost layer and the vibration damping layer. In addition, the surface layer and the back layer may be functional layers such as sound-absorbing layers, and in the case of a laminated structure of two or more layers, the material may include such functional layers.

[0135] Of these, a laminated sheet in which other layers are laminated on at least one side of the vibration damping layer is preferred in terms of improving workability, and a laminated sheet in which a surface layer is laminated on one side of the vibration damping layer and a back layer is laminated on the other side is particularly preferred in terms of improving workability and moldability of the vibration damping material. In particular, in the vibration damping material of the present invention, since the vibration damping layer contains a binder, the single-layer surface layer or back layer and the vibration damping layer can be tightly bonded without the need for an adhesive layer.

[0136] The surface layer and back layer may be, for example, wood-based boards (solid wood, plywood, wood fiberboard, etc.), inorganic boards (gypsum board, calcium silicate board, etc.), or synthetic resin sheets or films (polyolefin sheets, acrylic sheets, polyvinyl chloride sheets, polyester sheets, polyamide sheets, polyurethane sheets, etc.).

[0137] The thickness (average thickness) of the vibration damping material (layered vibration damping material) of the present invention may be 0.1 mm or more (particularly 0.3 mm or more), preferably 0.5 mm or more, more preferably 1 mm or more, and more preferably 2 mm or more (for example, 3 to 10 mm). If the thickness of the vibration damping material is too thin, there is a risk that the vibration damping performance will decrease.

[0138] The thickness (average thickness) of the surface layer or back layer may be 0.01 mm or more, for example, 0.01 to 1 mm, preferably 0.05 to 0.5 mm, and more preferably 0.1 to 0.3 mm.

[0139] [Vibration damping method] The present invention also includes a method (vibration control method) for installing the vibration-damping material in a building to suppress vibrations (especially vibrations originating from vibration sources).

[0140] In this method, the vibration damping material is simply placed at the vibration source that generates the vibration or at the location from which the vibration propagates from the vibration source. It is preferable to integrate and fix the vibration damping material and the vibration source or the location from which the vibration propagates.

[0141] In this invention, the vibration damping performance of a vibration damping material can be evaluated using typical indicators such as the loss coefficient η and the heavy floor impact sound level. Furthermore, the structure of the vibration damping material can be observed using AFM imaging, and its relationship to vibration damping performance can be evaluated.

[0142] In this specification and in the claims, the loss factor η, the weight floor impact sound level, and AFM (atomic force microscope) observations can be measured or evaluated by the methods described in the examples below. [Examples]

[0143] The present invention will be described in more detail below based on examples, but the present invention is not limited to these examples. Details of the materials of the vibration damping composition (or vibration damping material) used in the examples and the method of evaluating vibration damping (loss coefficient and AFM observation) are shown below.

[0144] [Materials for vibration damping compositions or vibration damping materials] (binder) Blown asphalt: "Blown Asphalt 10-20" manufactured by Idemitsu Kosan Co., Ltd., penetration (25℃) 16 (1 / 10 mm), softening point 110℃ (Vibration damping filler) Vibration damping filler A: C16AG (1,5-anhydro-D-glucitol-2,3,4,6-O-tetrapalmitate) synthesized in accordance with the method described in Japanese Patent Publication No. 6952305. Vibration damping filler B: C18AG (1,5-anhydro-D-glucitol-2,3,4,6-O-tetrastearate) synthesized in accordance with the method described in Japanese Patent Publication No. 6952305. Mica: "Chinese White Mica" manufactured by Tomoe Industrial Co., Ltd., 60 mesh (Filler) Calcium carbonate: Manufactured by Kochi Heavy Charcoal Co., Ltd., 200 mesh quality. Hollow microparticles: "Glass Balloon C20" manufactured by Tomoe Industrial Co., Ltd., median diameter 70 μm, bulk density 0.2 g / cm³ 3 (Surface layer and back layer) PET nonwoven fabric: Manufactured by Asahi Kasei Corporation, basis weight 50g / m² 2

[0145] [Evaluation methods for vibration control] <Loss Factor> The loss coefficient was measured in accordance with the central excitation method of JIS K 7391:2008 "Test method for vibration damping characteristics of unrestrained vibration-damping composite beams".

[0146] The base material was an aluminum plate (width 10 mm, length 250 mm, thickness 1 mm), and in each of the following examples, the sample was cast and molded to a thickness of 1 mm on the base material before being allowed to stand at room temperature. The measuring instruments used and the measurement conditions are summarized in Table 1.

[0147] [Table 1]

[0148] <Heavy floor impact sound level> A two-by-four construction floor was installed in the opening (dimensions 2740 × 3650 mm) of an acoustic laboratory (volume 61.6 m 3 , floor slab thickness 250 mm). Using a tire with standard heavy impact characteristics specified in JIS A 1418-2:2000 as the sound source, the heavy floor impact sound level was measured at 5 impact points and 5 sound receiving points. In the two-by-four construction floor, the floor was composed of floor joists: 210 lumber [455 mm spacing] and 15 mm thick tongue-and-groove plywood, the independent ceiling was composed of ceiling joists: 206 lumber and 12.5 mm thick gypsum board, and 50 mm thick glass wool [density 24 kg / m 3 was inserted in the ceiling cavity.

[0149] <AFM image> AFM observation was performed using an AFM (Oxford Instruments MFP-3D-BIO tapping mode) and a cantilever (Olympus OMCL-AC24OTS-W2). Based on the height image and the error signal image, changes in the structure of the vibration damping material depending on the presence or absence and type of the added vibration damping filler were observed, and the relationship with the vibration damping performance was evaluated.

[0150] [Example 1] Vibration damping filler A was added to about 20 g of blown asphalt heated to 200°C so as to account for 10% by mass in the vibration damping composition, and the mixture was stirred with a spatula for 3 minutes. The resulting mixture was allowed to stand at room temperature for 24 hours or more to prepare a vibration damping material, and the loss factor was calculated.

[0151] [Example 2] Except for changing damping filler A to damping filler B, the damping material was prepared in the same manner as in Example 1, and the loss coefficient was calculated.

[0152] [Comparative Example 1] Except for not adding a vibration-damping filler, a vibration-damping material (blown asphalt alone) was prepared in the same manner as in Example 1, and the loss coefficient was calculated.

[0153] [Reference example 1] Except for replacing the vibration-damping filler A with mica, the vibration-damping material was prepared in the same manner as in Example 1, and the loss coefficient was calculated.

[0154] Table 2 summarizes the detailed compositions of the vibration damping materials prepared in Examples 1-2, Comparative Example 1, and Reference Example 1, and the results are shown in Table 3.

[0155] [Table 2]

[0156] [Table 3]

[0157] Comparing the loss coefficients of Comparative Example 1 with Examples 1 and 2, there was no significant difference in the primary order, but the secondary and tertiary orders were larger in Examples 1 and 2, indicating that both damping fillers A and B functioned as damping fillers.

[0158] Comparing the loss coefficients in Examples 1 and 2, Example 2 had a larger loss coefficient, indicating that vibration damping filler B was more effective at improving vibration damping than vibration damping filler A.

[0159] Comparing the loss coefficients of Reference Example 1 and Example 1, Reference Example 1 had a larger loss coefficient at all orders, but the damping material in Example 1 also possessed a level of damping performance that was practically acceptable. Comparing the loss coefficients of Reference Example 1 and Example 2, Reference Example 1 had a larger loss coefficient at the first order, but there was no significant difference at the second and third orders.

[0160] Therefore, vibration-damping fillers A and B functioned as vibration-damping fillers on the nano to submicro order, and vibration-damping filler B (especially vibration-damping filler B in the second and third orders) contributed to improved vibration damping performance as a vibration-damping filler at almost the same level as mica (60 mesh).

[0161] Furthermore, the state of the damping material obtained was observed using AFM images, and its relationship with damping performance was evaluated.

[0162] Since it is difficult to directly observe the prepared vibration damping material using AFM, a sample for AFM observation was prepared as follows and considered to be equivalent to the prepared vibration damping material.

[0163] In each of the unheated blown asphalt samples from Examples 1-2, Comparative Example 1, and Reference Example 1, vibration-damping filler was added to the specified concentrations shown in Table 2. A small amount of each sample, mixed with a spatula for 3 minutes, was placed on a glass slide and heated on a 130°C hot plate for several minutes. The heated samples were spread thinly with a spatula and left at room temperature for 24 hours or more, after which AFM observation was performed. The results are shown in Figures 1A to 4B.

[0164] As is clear from Figures 1A, 1B, 2A, and 2B, in Examples 1 and 2, where vibration-damping fillers A and B were added to blown asphalt, respectively, the phases of the blown asphalt and vibration-damping fillers formed a microphase-separated structure. This suggests that the vibration-damping fillers alter the colloidal structure of the blown asphalt.

[0165] In Examples 1 and 2, it was confirmed that the vibration-damping filler formed fibers (particularly in Figures 1B and 2B). The average fiber diameter of these fibers was 100-200 nm, and they formed a three-dimensionally intertwined fibrous phase (long fibers or long fiber aggregates). In Example 2, the refinement or disappearance of structures derived from the asphaltene content in the asphalt (called Bee structures, which are rod-shaped structures with white and black stripes in the figures) was confirmed.

[0166] In other words, in both Example 1 and Example 2, fibers were formed in the blown asphalt, but in Example 1, a phase separation structure was formed in which Bee structures of about 10-20 μm were dispersed in an island-like manner within continuous fibers, whereas in Example 2, no clear separation of Bee structures was observed, and continuous fibers were observed throughout.

[0167] Based on these findings, it can be inferred that the proportion of fibers in the blown asphalt is greater in Example 2 than in Example 1, and the contact area with the blown asphalt is also larger, resulting in a higher loss coefficient and a higher vibration damping effect, which is consistent with the results shown in Table 3.

[0168] On the other hand, in Reference Example 1, the structure of the blown asphalt remained unchanged, suggesting that mica was agglomerating within the blown asphalt.

[0169] Therefore, it was suggested that vibration-damping fillers A and B alter the structure of the asphalt itself, and exert their vibration-damping properties through a mechanism different from conventional vibration-damping fillers such as mica.

[0170] [Example 3] 100 parts by mass of blown asphalt was heated and melted at 200°C, and 11 parts by mass of vibration damping filler B, 27 parts by mass of calcium carbonate, and 27 parts by mass of hollow fine particles were added and uniformly kneaded. The resulting composition was sandwiched between PET nonwoven fabrics on both sides and formed into a sheet. The obtained sheet-like molded body was cut into plates (910 mm long x 910 mm wide x 6 mm thick) and the vibration damping material (density 0.69 g / cm³) was used. 3 , areal density 4.1kg / m 2 A soundproofing layer with a thickness of 5.7 mm and a surface or back layer with a thickness of 0.15 mm was obtained. The obtained vibration damping material was laid over the entire surface of tongue-and-groove plywood on a two-by-four construction floor, flooring was laid on top of the vibration damping material, and fixed at 303 mm intervals using Unicloth screws (diameter φ3.8 mm x length L45 mm), and the heavy floor impact sound level was measured. The density of the vibration damping material was calculated by measuring the mass of the vibration damping material cut into 100 mm squares and using the following formula.

[0171] Density [g / cm 3 ] = amount of vibration-damping material [g] / (10 × 10 × thickness of test specimen [cm])

[0172] [Comparative Example 2] Flooring was laid on top of tongue-and-groove plywood of a 2x4 construction floor, and fixed at 303mm intervals using zinc-plated screws (diameter φ3.8mm x length L45mm), and the impact sound level of the heavy floor was measured.

[0173] [Comparative Example 3] Except for not adding a vibration-damping filler, the vibration-damping material (density 0.65 g / cm³) is the same as in Example 3. 3 , areal density 3.9kg / m 2 A soundproofing layer with a thickness of 5.7 mm and a surface or back layer with a thickness of 0.15 mm was prepared, and the impact sound level of heavy floors was measured.

[0174] Table 4 shows the heavy floor impact sound levels and their reduction amounts in Example 3 and Comparative Examples 2 and 3. The heavy floor impact sound level reduction amount was calculated based on the following formula, with the frequency band set to the 63 Hz band, which is the frequency band for determining the heavy floor impact sound level.

[0175] Reduction in heavy floor impact sound level = Heavy floor impact sound level without damping material [Comparative Example 2] - Heavy floor impact sound level with damping material [Example 3 or Comparative Example 3]

[0176] [Table 4]

[0177] As is clear from the results in Table 4, Example 3 and Comparative Example 3, which included vibration damping material, showed a reduction in heavy floor impact sound levels compared to Comparative Example 2, which did not include vibration damping material, indicating that the material functioned as a vibration damping agent. Furthermore, Example 3, which included vibration damping filler B, showed an even greater reduction in heavy floor impact sound levels than Comparative Example 3, which did not include vibration damping filler B, suggesting that vibration damping filler B was contributing to the vibration damping effect. [Industrial applicability]

[0178] The vibration-damping material containing the vibration-damping filler of the present invention can be used for vibration damping (or soundproofing) of buildings, roads, sound equipment, transportation equipment such as automobiles, industrial machinery, etc. For example, it can be installed in building components such as floors, ceilings, walls, and doors, or used as at least a part of such components. Of these, it is preferable that the vibration-damping material be installed in the floor or wall of a building.

Claims

1. A vibration-damping filler comprising a compound represented by the following formula (1). 【Chemistry 1】 [In the formula, group R is independently a hydrogen atom, an alkyl group having 10 or more carbon atoms, an alkylcarbonyl group having 10 or more carbon atoms, and the following formula (2): 【Chemistry 2】 (In the formula, n represents an integer between 8 and 18.) Selected from the group consisting of acyl groups represented by, Of the aforementioned groups R, at least one group R is either an alkylcarbonyl group having 10 or more carbon atoms, or an acyl group represented by formula (2). [m represents 0 or 1]

2. The vibration-damping filler according to claim 1, wherein in formula (1), the alkyl group having 10 or more carbon atoms of group R is a linear alkyl group having 10 to 22 carbon atoms, and the alkylcarbonyl group having 10 or more carbon atoms of group R is a linear alkylcarbonyl group having 10 to 22 carbon atoms.

3. In formula (1) above, group R is (i) independently a linear alkylcarbonyl group having 10 to 22 carbon atoms; or, (ii) The vibration-damping filler according to claim 1 or 2, wherein at least one of the groups R is an acyl group represented by formula (2).

4. The vibration-damping filler according to claim 1 or 2, wherein in formula (1), there is one or fewer groups R representing hydrogen atoms.

5. In formula (1) above, group R is (i) independently a linear alkylcarbonyl group having 12 to 20 carbon atoms; or, (ii) The vibration-damping filler according to claim 1 or 2, which is independently an acyl group represented by formula (2).

6. The vibration damping filler according to claim 1 or 2, wherein in formula (2), n is an integer from 10 to 16.

7. The vibration-damping filler according to claim 1 or 2, wherein the compound represented by formula (1) is a compound represented by the following formula (3) or (4). 【Transformation 3】 (In the formula, base R is the same as in formula (1) above.) 【Chemistry 4】 (In the formula, base R is the same as in formula (1) above.)

8. A vibration damping composition comprising at least the vibration damping filler according to claim 1 or 2 and a binder.

9. The vibration damping composition according to claim 8, comprising the vibration damping filler in a proportion of 0.05 to 50 parts by mass per 100 parts by mass of the binder.

10. The vibration damping composition according to claim 8, wherein the binder comprises asphalt.

11. A vibration damping material formed from the vibration damping composition described in claim 8, wherein the compound represented by formula (1) forms a fibrous phase.

12. The vibration damping material according to claim 11, wherein the average fiber diameter of the fibers in the fiber phase is 10 to 500 nm, and the ratio of the average fiber length to the average fiber diameter of the fibers in the fiber phase (average fiber length / average fiber diameter) is 10 or more.

13. A method for producing a vibration damping material according to claim 11, comprising heating and mixing at least a binder and a vibration damping filler according to claim 1 or 2.

14. A method for suppressing vibrations originating from vibration sources by installing the vibration damping material described in claim 11 in a building.

Citation Information

Patent Citations

  • Damping material

    JP2019044173A

  • Asphalt modifier and composition containing the same

    JP2023041636A